Prebiotic properties, antioxidant activity, and acute oral toxicity of xylooligosaccharides derived enzymatically from corncob. (April 2021) - Boonchuay, Pinpanit; Wongpoomchai, Rawiwan; Jaturasitha, Sanchai; Mahatheeranont, Sugunya; Watanabe, Masanori; Chaiyaso, Thanongsak
Abstract: In this study, corncob xylooligosaccharides (corncob-XOS) were prepared enzymatically, and their beneficial effects, compared to commercial prebiotics, including fructooligosaccharides (FOS), gentiooligosaccharides (GTO), inulin, isomaltooligosaccharides (IMO), lactulose, and commercial xylooligosaccharides (commercial-XOS), were assessed. The prebiotic property of corncob-XOS, in which they enhance the growth of probiotic lactic acid bacteria (LAB), namely Lactobacillus casei TISTR1463, L. delbrueckii subsp. lactis TISTR1464, and L. plantarum TISTR1465, was tested. The result revealed that this prebiotic is a good carbon source due to its ability to promote growth and induce β-xylosidase production in all tested strains. Corncob-XOS showed excellent 2, 2′-diphenyl-1-picryl-hydrazyl (DPPH) and 2, 2′-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical scavenging activities as well as ferric reducing antioxidant power (FRAP), and the total phenolic compound content was remarkably high. The in vivo acute oral toxicity of corncob-XOS, based on behavioral alterations and the mortality of rats, was investigated. There was no significant toxic effect on body weight (bw), vital organ weight, or essential parameters of blood at the single dose level of 5000 mg/kg bw at p > 0.05. Furthermore, the median lethal dose (LD50 ) of corncob-XOS suggests that they are non-toxic. Taken together, these results support the further application of corncob-XOS as alternative forms of functional foods. Graphical abstract: Image 1 Highlights: Corncob-XOS with high xylobiose content were achieved using purified xylanase_1948. Prebiotic properties of corncob-XOS were comparable to commercial-XOS. Corncob-XOS exhibited the excellent antioxidant activity. Corncob-XOS were non-toxic prebiotics based on in vivo acute oral toxicity tests.